1994
DOI: 10.1146/annurev.iy.12.040194.002213
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Analogs/MHC Complexes as Specific T Cell Receptor Antagonists

Abstract: Recent studies demonstrated that antigen analogs can act as powerful and specific inhibitors of T cell activation, leading to the formulation of the concept that antigen analog/MHC complexes may act as antagonists of the T cell receptor (TCR). TCR antagonism appears to be associated with engagement of the TCR below a crucial affinity threshold necessary for full T cell activation. Studies addressing the molecular mechanism of this effect suggest that TCR antagonists could act by interfering with membrane-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(72 citation statements)
references
References 0 publications
2
70
0
Order By: Relevance
“…Supporting this contention, de Carvalho Nicacio et al found MHC-specific differences in proliferation magnitude to recombinant Puumala virus N-Ag in inbred strains of laboratory house mice (48). In addition, some viral peptides are antagonistic to T cell responses, such that they can impact effector T cell maturation (53)(54)(55). Such antagonism can lead to regulatory T cell activation and bystander suppression of an inflammatory immune response (56).…”
Section: Discussionmentioning
confidence: 98%
“…Supporting this contention, de Carvalho Nicacio et al found MHC-specific differences in proliferation magnitude to recombinant Puumala virus N-Ag in inbred strains of laboratory house mice (48). In addition, some viral peptides are antagonistic to T cell responses, such that they can impact effector T cell maturation (53)(54)(55). Such antagonism can lead to regulatory T cell activation and bystander suppression of an inflammatory immune response (56).…”
Section: Discussionmentioning
confidence: 98%
“…The formation of such complexes has been observed for a variety of proteins and, in some cases, is essential for normal function (23). For instance, oligomerization of the T-cell receptor after interaction with antigen bound to major histocompatability complex is thought to be a necessary event for downstream signaling and immunosurveillance (27,28). Within the field of AD-related research, the N-and C-terminal fragments of presenilin 1 have been shown to be components of a high molecular weight complex containing ␤-catenin that has been implicated in apoptosis (29 -32).…”
Section: Discussionmentioning
confidence: 99%
“…The argument against the classical model of competitive inhibition of agonist binding to the receptor has been the fact that there are more TCRs than there are agonist and antagonist-MHC complexes, thereby making it impossible to saturate the TCRs of a cell with antagonist peptide (14,31). However, there are two considerations that mitigate this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in TCR affinity for an epitope are typically accomplished by a single conservative amino acid substitution at a TCR contact site. The initial reports that such altered peptide ligands (APL) 3 could strongly affect the outcome of TCR engagement with peptide-MHC complexes demonstrated partial agonist activity (cytokine production in the absence of proliferation) (12) or antagonist activity whereby stimulation of T cells by agonist could be inhibited by the addition of certain APLs to cultures containing Ag-pulsed APCs and T cells (13,14). The mechanism by which inhibition of T cell activation is accomplished by such antagonist APLs remains unresolved.…”
Section: Study Of the Mechanism Of Tcr Antagonism Using Dual-tcr-exprmentioning
confidence: 99%